Cellular Response In The Development Of Atherosclerosis By Gynura Procumbens - Manogaran, Manimegalai (2021)
Atherosclerosis is the main fundamental root of cardiovascular disease (CVD) caused by a chronic inflammatory of blood vessels, namely atherosclerosis which induced by oxidised low-density lipoprotein (oxLDL) and leukocytes. Gynura procumbens or locally called as sambung nyawa has cardio-protective effect. The current study was undertaken to elucidate the chemical constituents of G. procumbens ethanol extract and its fractions, their effects on macrophage derived foam cells formation and CD4+ T cell differentiation. Firstly, LC-MS analysis detected bioactive constituents from group of fatty acid, flavonoid, sesquiterpenoids and products of chlorophyll breakdown whereby GC-MS showed that G. procumbens ethanol extract and its fractions contained varied volatile compounds such as hexadecane, phytol and stigmasterol. G. procumbens ethanol extract and its fractions exhibited potent cell viability as all the concentrations induced proliferation of RAW264.7 macrophages as the percentages of cell viability were above 100% compared to untreated cells. Secondly, G. procumbens ethanol extract and its fractions reduced lipid droplet accumulation and total cholesterol in oxLDL-treated macrophages together with significant reduction of TNF-α and IL-1β secretions in their supernatant. In addition, G. procumbens ethanol extract and its fractions significantly reduced LOX-1 gene expression and increased ABCA-1 gene in oxLDL-treated macrophages. Finally, G. procumbens ethanol extract and its fractions up-regulated the expression of CD11c, MHC class II and CD80 in oxLDL-loaded BMDC. G. procumbens ethanol extract and its fractions suppressed T-bet, GATA-3 and RORγt gene expression but increased the expression of Foxp3 gene in differentiated CD4+ T cells. Furthermore, G. procumbens ethanol extract and its fractions also increased DLL-3 gene but suppressed Jagged-1 gene expression in activated BMDC. In conclusion, G. procumbens ethanol extract and its fractions possess anti-atherogenic effect via inhibiting cellular components involve in atherogenesis, thus give clear insight for the development of novel therapeutic target for atherosclerosis treatment.